Dampak Pendekatan Saintifik terhadap Sikap Spiritual Siswa dalam Pembelajaran PAI di SMA di Sidoarjo - Rangga Sa'adillah S.A.P.; Tobroni Tobroni; Ishomuddin Ishomuddin; Khozin Khozin (UIN Sunan Ampel Surabaya, 2019)
This study aims to describe the impact of a scientific approach on students' spiritual attitudes. Through the constructivism paradigm combined with a phenomenological approach, this study involved 19 students. In-depth interviews are used as the main data collection technique while observation and documentation as secondary techniques as well as data validation. The analysis phase is carried out with four stages namely description of the phenomenon, horizonalization, cluster of meaning, essence description. This study reveals that a scientific approach can provide three impacts on students' spiritual attitudes, namely the impact on cognitive, affective, and psychomotor spiritual attitudes. Spiritual attitudes found in the research act as driving forces for human behavior. The findings of this study develop the interaction of character components. The components of a spiritual attitude are interactions not determinants. This means that the components of spiritual attitude only correlate with each other and these components will not be able to validly predict behavior.